2018
DOI: 10.1111/ped.13520
|View full text |Cite
|
Sign up to set email alerts
|

Food‐dependent exercise‐induced anaphylaxis in Japanese elementary school children

Abstract: FDEIA was far less common in elementary school than in junior-high school, and wheat was the major causative food. The new appearance of DEIA was notable. Decreasing episode recurrence remains an issue that needs to be resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
0
9
0
4
Order By: Relevance
“…Une étude effectuée en 2013 par questionnaire auprès des infirmières de 317 écoles primaires de Yokohama portant sur 170 146 enfants a permis de suspecter 33 cas d'AAIE avec seulement 8 observations confirmées (7 garçons/1 fille). La prévalence estimée est donc de 0,0047% ou encore 1/20 000 enfants (10). Les allergènes alimentaires concernés étaient le blé (4), les crustacées (1), le calamar (1), le soja (1) et « fruits » (1).…”
Section: éPidémiologieunclassified
See 1 more Smart Citation
“…Une étude effectuée en 2013 par questionnaire auprès des infirmières de 317 écoles primaires de Yokohama portant sur 170 146 enfants a permis de suspecter 33 cas d'AAIE avec seulement 8 observations confirmées (7 garçons/1 fille). La prévalence estimée est donc de 0,0047% ou encore 1/20 000 enfants (10). Les allergènes alimentaires concernés étaient le blé (4), les crustacées (1), le calamar (1), le soja (1) et « fruits » (1).…”
Section: éPidémiologieunclassified
“…Cette même équipe japonaise a comparé la prévalence de l'AAIE dans une population plus âgée puisque cette étude concerne 76 534 étudiants de Yokohama (11). La prévalence de l'AAIE s'élève à 0,018% soit 14 cas ou encore 18/10 000 (10). Le sexe ratio est de 1.…”
Section: éPidémiologieunclassified
“…OIT for CM or wheat effectively achieves desensitization, 6‐9 but exercise after ingestion of the causative antigen can cause immediate allergic symptoms 10‐14 . Manabe et al suggested two types of exercise‐induced allergic symptoms: "food‐dependent exercise‐induced anaphylaxis" 15 and "desensitization status and exercise‐induced anaphylaxis" 10,16 …”
Section: Introductionmentioning
confidence: 99%
“…Wheat is the most common cause of FDEIA, but other grains, seafood, peanut, egg, milk, Rosaceae fruits and vegetables have also been reported as causes of FDEIA. 2 3 In some cases, symptoms may be triggered by any meal followed by exercise regardless of the food type. 4 Although FDEIA is frequently reported in young adults, epidemiologic studies are rare.…”
mentioning
confidence: 99%
“…A Japanese group reported the prevalence of FDEIA at 0.017% among junior high school students and 0.0047% among elementary school students. 2 5 In a multicenter anaphylaxis registry in Korea, the proportion of FDEIA was 1.2% and 3.1% in children and adults, respectively. 6 Recently, the concept of FDEIA has been expanded and described as “food-dependent cofactor-augmented anaphylaxis” or “cofactor-induced food allergy.” 7 8 Reported cofactors other than physical exercise are aspirin, other analgesics, alcohol, stress, and infections.…”
mentioning
confidence: 99%